Adjusted donor age: a clinical score to support organ acceptance decisions in deceased-donor kidney transplantation - Bright, Rupert; Mahler, Christoph; Adwaney, Anamika; Dosani, Dhriti; Morganti, Emma; Friedl, Felix; Nußhag, Christian; Speer, Claudius; Benning, Louise; Göth, Daniel; Schaier, Matthias; Sommerer, Claudia; et al. (Transplant international, 2024)
As transplant programmes have evolved to allow a wider donor pool, organ acceptance decisions have become increasingly complex and lack transparency and equality. Clinical scoring tools exist but there is limited consensus on their use. From a prospective observation of consecutive deceased-donor kidney offers in a large urban transplant centre, a simple score was developed based on donor age and other risk characteristics, excluding ischemia time and graft histology. The score was validated in subsequent cohorts of consecutive offers in the UK and Germany. In the development cohort of 389 kidney offers, 110 (28%) were transplanted and 175 (45%) declined. Nine risk factors were incorporated into a score based on age, but adjusted for the number of risk factors present, making an 'adjusted donor age', with offers separated into equal quintiles by decade. The score was validated in a UK cohort of 380 subsequent offers, and a German cohort of 431 offers. In both cohorts adjusted donor age discriminated between favourable and poor post-transplant outcomes (C-statistic 0.77 in the UK, 95%CI 0.65-0.88, and 0.71 in Germany, 95%CI 0.64-0.77). Adjusted donor age is a simple score quantifying deceased donor kidney quality, which is consistent with current practice and predicts post-transplant outcome.